Plastic Waste Contribution in Concrete Strength Improvement At Early and Long Curing Ages - H. ALfahdawi, V; A. Osman, S.; Hamid, R.; Ismail AL-hadithi, Abdulkader (International Journal of Engineering and Technology, 2019)
In general, the concrete suffering of brittleness and weakness to resist the direct and tensile stresses.Â In Malaysia, millions of tons of the polyethylene terephthalate (PET) plastic waste accumulated from the single use of drinking water bottles, its accumulation creates threat on the civilian life and the environment. Inclusion of shredded PET waste in concrete may help mitigate the negative impact of plastic waste on the environment and further produce green/sustainable concrete and solve the weakness of tensile strength. In current research, 0.0 to 1.75% of coarse aggregate weight was replaced by PET waste to delve into the behavior of low velocity impact strength of concrete containing PET at early and long curing age. It was positive that some of the ratios helped to enhance the impact strength at age 28 days, where the number of blows increased to 80%, and at age 90 days, the number of blows increased up to 4 times compared with age 28 days. The results exhibited to the possibility of utilizing PET waste by low volumes to produce new concrete has good strength and contributes in reducing the plastic waste negative impact on the environment.Â